Chitosan modified with 1, 3, 4-oxa(thia)diazole derivatives with high efficacy to heal burn infection by Staphylococcus aureus. (May 2018) - Salahuddin, Nehal; Elbarbary, Ahmed; Allam, Nanis G; Hashim, Ayat F
Chitosan has been modified through the reaction of chitosan with 5-phenyl-1, 3, 4-oxadiazole-2-thiol (I); 5-amino-1, 3, 4-thiadiazole-2-thiol (II); and 5-(4 chlorophenyl)-1, 3, 4-thiadiazole-2-thiol (III). Fourier transform infrared spectroscopy spectra and 1 H-NMR demonstrated the interaction between 1, 3, 4-oxa(thia)diazoles and chitosan. The Gram-negative bacteria ( Escherichia coli ATCC 8739, Aeromonas hydrophila, Shegilla sp.), Gram-positive bacteria ( Staphylococcus aureus, Bacillus subtilis ATCC 6633), yeast ( Candida albicans ), and the filamentous fungi ( Aspergillus niger ) were used to examine the antimicrobial activity of the modified chitosan by well diffusion method. The results indicated that modified chitosan possess better inhibitory property than chitosan. Furthermore, in vivo study was performed on burned mouse model wound infection by S. aureus NCTC 6356. Modified chitosan improved antimicrobial efficacy against fatal burn infections in comparison with chitosan.